Thrombus Migration and Fragmentation After Intravenous Alteplase Treatment: The INTERRSeCT Study - Ohara, Tomoyuki; Menon, Bijoy K; Al-Ajlan, Fahad S; Horn, MacKenzie; Najm, Mohamed; Al-Sultan, Abdulaziz; Puig, Josep; Dowlatshahi, Dar; Calleja Sanz, Ana I; Sohn, Sung-Il; Ahn, Seong H; Poppe, Alexandre Y; et al. (Stroke, 2021)
BACKGROUND AND PURPOSE: There is interest in what happens over time to the thrombus after intravenous alteplase. We study the effect of alteplase on thrombus structure and its impact on clinical outcome in patients with acute stroke. METHODS: Intravenous alteplase treated stroke patients with intracranial internal carotid artery or middle cerebral artery occlusion identified on baseline computed tomography angiography and with follow-up vascular imaging (computed tomography angiography or first run of angiography before endovascular therapy) were enrolled from INTERRSeCT study (Identifying New Approaches to Optimize Thrombus Characterization for Predicting Early Recanalization and Reperfusion With IV Alteplase and Other Treatments Using Serial CT Angiography). Thrombus movement after intravenous alteplase was classified into complete recanalization, thrombus migration, thrombus fragmentation, and no change. Thrombus migration was diagnosed when occlusion site moved distally and graded according to degrees of thrombus movement (grade 0-3). Thrombus fragmentation was diagnosed when a new distal occlusion in addition to the primary occlusion was identified on follow-up imaging. The association between thrombus movement and clinical outcome was also evaluated. RESULTS: Among 427 patients in this study, thrombus movement was seen in 54% with a median time of 123 minutes from alteplase administration to follow-up imaging, and sub-classified as marked (thrombus migration grade 2-3 + complete recanalization; 27%) and mild to moderate thrombus movement (thrombus fragmentation + thrombus migration grade 0-1; 27%). In patients with proximal M1/internal carotid artery occlusion, marked thrombus movement was associated with a higher rate of good outcome (90-day modified Rankin Scale, 0-2) compared with mild to moderate movement (52% versus 27%; adjusted odds ratio, 5.64 [95% CI, 1.72-20.10]). No difference was seen in outcomes between mild to moderate thrombus movement and no change. In M1 distal/M2 occlusion, marked thrombus movement was associated with improved 90-day good outcome compared with no change (70% versus 56%; adjusted odds ratio, 2.54 [95% CI, 1.21-5.51]). CONCLUSIONS: Early thrombus movement is common after intravenous alteplase. Marked thrombus migration leads to good clinical outcomes. Thrombus dynamics over time should be further evaluated in clinical trials of acute reperfusion therapy.
Keywords: senioři; Carotid Artery, Internal; Treatment Outcome; Stroke; senioři nad 80 let; computed tomography angiography; reperfuze; Intracranial Thrombosis; Infarction, Middle Cerebral Artery; Tomography, X-Ray Computed; výsledek terapie; Administration, Intravenous; Fibrinolytic Agents; Middle Aged; Thrombolytic Therapy; mužské pohlaví; Tissue Plasminogen Activator; reperfusion; tkáňový aktivátor plazminogenu; cévní mozková příhoda; fibrinolytika; intravenózní podání; Aged, 80 and over; ženské pohlaví; intrakraniální trombóza; Humans; CT angiografie; stenóza arteria carotis; angiography; internal carotid artery; lidé středního věku; Computed Tomography Angiography; trombolytická terapie; Carotid Stenosis; počítačová rentgenová tomografie; Aged; Female; Reperfusion; arteria carotis interna; lidé; Male; infarkt arteria cerebri media; middle cerebral artery